PENGETAHUAN GIZI DAN INDEKS MASSA TUBUH TERHADAP RESIKO KEK PADA REMAJA PUTRI - Arief, Ria Qadariah; Widayanti, Linda Prasetyaning (Jurnal Kesehatan, 2025)
The problem of CED in adolescent girls not only impacts individual health, but also has long-term consequences, especially in terms of reproductive health and the quality of future generations. Adolescent girls who experience CED are at risk of giving birth to children with low birth weight (LBW), which in turn can increase the risk of stunting. Therefore, efforts to prevent CED from adolescence are very important to break the chain of intergenerational nutritional problems. This study aims to analyze the relationship between the level of nutritional knowledge and BMI status on the risk of CED in adolescent girls. A cross-sectional study was used to analyze the phenomenon of an increasing trend in the incidence of CED based on Body Mass Index and a description of the knowledge possessed by young women at a certain point in time. This research involved 40 teenage female respondents aged 17-19 years (late adolescent age group). The results show a significant relationship between BMI and CED risk, with a p value of 0.011. All young women who had a BMI in the thin category were identified as having a high risk of CED, while the majority of respondents with a normal BMI (68.2%) were not at risk of CED. These results indicate that BMI status is a strong predictor factor in determining the risk of CED